Scalable synthesis of 3-Ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one: an important building block of the antidiabetic drug glimepiride - Chavan, Subhash P.; Pawar, Ambaji A.; Patil, Niteen B.; Kadam, Appasaheb L.; Shinde, Shrikrishna S. (Synthesis-Stuttgart, 2020)
A four-step, practical, and easily scalable synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one, an important building block of the antidiabetic drug glimepiride, has been accomplished. Key features are the synthesis of 3-methyl-4-hydroxy-2-butenolide in water and triflic acid mediated N-benzyl lactam N-deprotection. The main advantages of this process are the scalable synthetic route and decreased number of reaction steps, which paves the way for the industrial-scale synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one.
Keywords: antidiabetic drug; Butenolide; glimepiride; lactams; scalable synthesis